EFFORTS TO IMPROVE CHILDREN'S EXPRESSIVE LANGUAGE DEVELOPMENT THROUGH ROLE-PLAY ACTIVITIES AT THE AGE OF 4-5 YEARS AT AL-FAUZAN PAUD, TENJOAYU VILLAGE, TANARA DISTRICT, SERANG REGENCY - Endang Fatimah; Novita Sari; Inten Risna; Amat Hidayat; Mutia Sari (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This research is motivated by the limited expressive language skills of most children aged 4–5 years at the Al-Fauzan PAUD, Tenjoayu Village, Tanara, Serang Regency. The purpose of the research is to examine the implementation of role-playing activities in improving the expressive language development of early childhood. The method used is descriptive qualitative with primary and secondary data sources. Data collection techniques include in-depth interviews, observation, and documentation to obtain a comprehensive picture of the research focus. Data analysis of this research refers to the qualitative approach of Miles & Huberman which emphasizes the stages of data reduction, data presentation, and drawing conclusions so that the research results reflect the real social context. The results of the study indicate that role-playing activities make a significant contribution to improving children's expressive language skills. Theoretically, the results of this study are supported by Vygotsky's view of the Zone of Proximal Development (ZPD) which emphasizes the importance of social interaction and the role of teachers in helping children achieve higher language skills. The conclusion of the study shows that role-playing activities at the Al-Fauzan PAUD are implemented through planning, implementation, and evaluation stages with a thematic approach that is appropriate to the characteristics of children aged 4–5 years. This activity effectively improves vocabulary, the use of complete sentences, and children's confidence in speaking